Association of Changes in Effusion‐Synovitis With Progression of Cartilage Damage Over Eighteen Months in Patients With Osteoarthritis and Meniscal Tear. Issue 1 (29th November 2018) - MacFarlane, Lindsey A.; Yang, Heidi; Collins, Jamie E.; Jarraya, Mohamed; Guermazi, Ali; Mandl, Lisa A.; Martin, Scott D.; Wright, John; Losina, Elena; Katz, Jeffrey N.; ,
Abstract : Objective: Synovitis is a feature of knee osteoarthritis (OA) and meniscal tear and has been associated with articular cartilage damage. This study was undertaken to examine the associations of baseline effusion‐synovitis and changes in effusion‐synovitis with changes in cartilage damage in a cohort with OA and meniscal tear. Methods: We analyzed data from the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial of surgery versus physical therapy for treatment of meniscal tear. We performed semiquantitative grading of effusion‐synovitis and cartilage damage on magnetic resonance imaging, and dichotomized effusion‐synovitis as none/small (minimal) and medium/large (extensive). We assessed the association of baseline effusion‐synovitis and changes in effusion‐synovitis with changes in cartilage damage size and depth over 18 months, using Poisson regression models. Analyses were adjusted for patient demographic characteristics, treatment, and baseline cartilage damage. Results: We analyzed 221 participants. Over 18 months, effusion‐synovitis was persistently minimal in 45.3% and persistently extensive in 21.3% of the patients. The remaining 33.5% of the patients had minimal synovitis on one occasion and extensive synovitis on the other. In adjusted analyses, patients with extensive effusion‐synovitis at baseline had a relative risk (RR) of progression of cartilage damage depth of 1.7 (95% confidence interval [95% CI] 1.0–2.7). Compared to those with persistently minimal effusion‐synovitis, those with persistently extensive effusion‐synovitis had a significantly increased risk of progression of cartilage damage depth (RR 2.0 [95% CI 1.1–3.4]). Conclusion: Our findings indicate that the presence of extensive effusion‐synovitis is associated with subsequent progression of cartilage damage over 18 months. The persistence of extensive effusion‐synovitis over time is associated with the greatest risk of concurrent cartilage damage progression.